2014
DOI: 10.5414/cn108014
|View full text |Cite
|
Sign up to set email alerts
|

Hourly oral sodium chloride for the rapid and predictable treatment of hyponatremia

Abstract: Hypertonic NaCl is first-line therapy for acute, severe and symptomatic hyponatremia; however, its use is often restricted to the intensive care unit (ICU). A 35-year-old female inpatient with an optic chiasm glioma and ventriculoperitoneal shunt for hydrocephalus developed acute hyponatremia (sodium 122 mEq/L) perhaps coinciding with haloperidol treatment. The sum of her urinary sodium and potassium concentrations was markedly hypertonic vis-à-vis plasma; it was inferred that serum sodium concentration would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…This exercise shows that the required sodium load can far exceed a typical starting dose of NaCl, like 1 gram by mouth 3 times a day. There is even a precedent for salt tablets being given hourly (34). Inadvertent underdosing may explain why salt tablets may not seem to work at times in hyponatremia (35).…”
Section: Resultsmentioning
confidence: 99%
“…This exercise shows that the required sodium load can far exceed a typical starting dose of NaCl, like 1 gram by mouth 3 times a day. There is even a precedent for salt tablets being given hourly (34). Inadvertent underdosing may explain why salt tablets may not seem to work at times in hyponatremia (35).…”
Section: Resultsmentioning
confidence: 99%
“…At this time, only half doses of furosemide and hydrocortisone were administered. According to the total amount of urine sodium excretion, respectively, to give their 8–12 g of sodium chloride tablet per day (Kerns et al, 2014 ), and serum sodium was maintained at a normal level. The follow-up 3 months after injury showed that all patients were discharged and that the serum sodium levels, plasma osmolality and urine flow rate (ml/d) were in the normal range (Table 3 ) with a continuous sodium supplementation program, while the daily liquid intake was limited to no more than 1,000 ml (Furst et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, all the therapies try to add more Na/K solutes (salt tablet, KCl, NS, and hypertonic saline) or try to remove free water (loop diuretic, urea, V 2 -receptor antagonist, make insensible losses > fluid restriction). [14][15][16][17][18][19][20][21][22][23]…”
Section: Edelman Equation Symbolizes [Sodium] Physiologymentioning
confidence: 99%